P08.01 Characterising cd4+ and cd8+ t-cell responses by intracellular cytokine staining in women with and without chlamydia trachomatis reinfection. (13th September 2015) - Jordan, SJ; Kapil, R; Sabbaj, S; Geisler, WM
Abstract : Background: Chlamydia trachomatis (CT) infection is the most prevalent bacterial sexually transmitted infection worldwide and, untreated, can lead to significant reproductive morbidity. Unfortunately, the prevalence remains high in the United States and no effective CT vaccine exists, in part because of an inadequate knowledge of immunological responses to CT infection in humans and, specifically, no correlates of protective immunity to guide vaccine studies. In animal studies, IFN-γ and/or TNF-α producing CD4 cells are known to mediate protection against C. trachomatis . The objective of this study was to characterise the T-cell mediated immune responses to C. trachomatis in humans with and without CT reinfection at a follow up clinic visit. Methods: In an ongoing study, peripheral blood mononuclear cells (PBMCs) are collected from CT-infected women at the time of treatment and stimulated in vitro with C. trachomatis antigens MOMP or PGP3, then fixed and permeabilized. The percentage of CD4 + and CD8 + T-cells expressing either IFN-γ or TNF-α is then assessed using intracellular cytokine staining (ICCS) and flow cytometry. Women return at 3- and 6-months for repeat genital chlamydia screening. Cytokine-specific ICCS responses are then compared in women with versus without subsequent CT reinfection at follow-up to assess for possible correlates of protection. Results: To date, we have performed ICCS on 44 women who have completed the study. Compared with women who had CT reinfection at a follow-up visit (n = 14), women without CT reinfection (n = 30) had higher baseline positive CD8 + TNF-α responses (p = 0.042). There was no significant association of IFN-γ and/or TNF-α CD4 responses with CT reinfection risk. Conclusions: Our preliminary findings reveal that a TNF-α-producing CD8 + T-cell response appears to correlate with a decreased risk for CT reinfection, suggesting a possible role in protective immunity. CD4 T-cell responses have not significantly differed in women with versus without CT reinfection. Disclosure of interest statement: Nothing to declare.